Biofuel production in Latin America: A review for Argentina, Brazil, Mexico, Chile, Costa Rica and Colombia - Lina Patricia Vega; Karen Tatiana Bautista; Heliana Campos; Sebastian Daza; Guillermo Vargas (Energy Reports, 2024)
Natural resources deterioration, as well as greenhouse gas (GHG) emissions are a critical global problem, derived mainly from the use of fossil fuels. In recent years, several Latin American countries have sought alternatives to replace fuels with biofuels. In this regard, this article aims to make a bibliographic review focused on the analysis of the current situation of biofuel production and research development in Argentina, Brazil, Mexico, Chile, Costa Rica and Colombia. For this, seventy-seven investigations extracted in the last ten years from the databases ResearchGate, ScienceDirect, MDPI, Academic Google, Scopus, ScienceDirect, EBSCO and Elsevier were analyzed. Also, and for the same period, a bibliometric analysis of 355 investigations of the Web of Science database was carried out. The article presents the production figures, technologies, advances and challenges for the production of biofuels in these countries. Brazil stands out as a leader in the region and stands out worldwide in the generation of clean energy through the implementation of a biofuels policy and its incorporation into the transport sector. From this review, it is possible to know the state of production and research on biofuels in these countries and the challenges they face in achieving advances that do not reflect the comparative advantages they have due to the availability of raw materials for their production.